IDENTIFIKASI STRUKTUR SENYAWA ANTIJAMUR DARI RUMPUT LAUT - Rahmawati Rahmawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
Screening of plants antifungal compounds from Algae has been resulted. Screening was preceded by extraction of its fresh substance with benzene, methanol, and chloroform solvents and followed examination towards fungi Fusarium oxysforum, Sclerotium rolfsii, Aspergillus flavus, and Pythium spp. The antifungal effects were tested by well methode in potato dextrosa agar (PDA) medium. Analysis compound of benzene extract with preparative TLC methode (n-hexene : ethyl acetate : methanol = 7 : 2 : 1) obtained 5 compounds. Antifungal activity test of the fractions was done by the disk diffution methode with PDA medium. Identification of active compounds with spectroscophy method (IR and NMR) indicated the benzene extract analogue with fungicide Metalaxyl with the benzene ring and substituens of ester, alkyl, and amide. Identification of fractions showed that the compounds analogue with fungicides belong to carboxamide with the main substituen of benzene ring and ester/aldehids formed, alkyl, and  amide.